PENGARUH TERPAAN IKLAN SHOPEEBABY SHARK VERSI PRILLY ‘ADA SHOPEE, SELALU DI HATI’ TERHADAP BRAND AWARENESS SHOPEE - Astiti Sari, Ni Kadek Diah; Pascarani, Ni Nyoman Dewi; Alit Suryawati, Dr. I Gusti Agung (E-Jurnal Medium, 2019)
ABSTRACT   As many as 70% of the people of Denpasar City still use television as a media in seeking information.Shopee uses baby shark songs that have been viral and Prilly as the millennial generation representative in the advertisement because 51% of Shopee stakeholders are millennial generation.The purpose of this study was to determine the effect of exposure to Prilly version of Shopee advertisement on the brand awareness of Shopee in the millennial generation in Denpasar City.The theory used in this study is Dennis McQuail's Stimulus Organism Theory.This type of research is quantitative associative.The findings in this study, the stimulus of Shopee advertising exposure to the millennial generation in the city of Denpasar only reached  conviction stage.Because, in the act of using services or actions (actions) the millennial generation of Denpasar City has a low level or rarely in the use of Shopee services.With a moderate level of relationship, exposure to Shopee ads has a low influence but positif and significant on Shopee brand awareness     Keywords : brand awareness,millenial,Shopee, Television,